Mandinga: Power and deception in Afro-Brazilian capoeira - González Varela, Sergio (Social Analysis, 2013)
This article is about the meaning of mandinga in Afro-Brazilian capoeira as it is practiced in the city of Salvador, Brazil. Capoeira is an art form that combines elements of ritual, play, and fight. My main argument focuses on the mandinga as an indigenous form of power that shapes social relations, bodily interaction, magic acts, and the definition of a person. The concept of mandinga offers an understanding of the deceptive logic of capoeira and contributes to the development of an ethnographic theory of power. The emphasis here is on the importance of mandinga as a strategy for fighting and as a principle for social interaction with strong ontological implications. It is considered a cosmological force that affects the foundations of subjective reality and the perception of the world. © Berghahn Journals.
Created from Fastlane, Scopus look-up
Keywords: Bodily techniques; Capoeira Angola; Cosmology; Ethnographic theory; Mandinga; Ontology; Performance; Power